Efeitos de uma molécula híbrida de resveratrol e curcumina na carcinogênese colorretal - Baptistella, Mariane Minussi (2021)
The approaches used in cancer treatment imply costly expenses for the health system and the nonspecific action of chemotherapy is related to a series of adverse effects. Considering such impasses, and based on scientific evidence of the efficacy of resveratrol and curcumin in molecular pathways that lead to carcinogenesis, the aim of the current study was to evaluate the possible chemopreventive and/or chemotherapeutic effects of a hybrid resveratrol and curcumin molecule [ (E)-3-(4- hydroxy-3-methoxyphenyl)-N'-(4-methoxybenzylidene) acrylhydrazide - PQM162] in colorectal carcinogenesis. In the in vivo test system, Wistar rats were treated with PQM162 at doses of 0.5; 1.0 and 2.0 mg/kg body weight (b.w.) in three different treatment approaches for 6 weeks: simultaneous, pre-treatment and post-treatment. Preneoplastic lesions were induced with 1,2-dimethylhydrazine (DMH, 160 mg/kg p.c.). The frequency aberrant crypt foci (ACF), aberrant crypts (AC) were evaluated, as well as the evaluation of gene expression by RT-PCR (reverse-transcriptase polymerase chain reaction) and immunohistochemistry to elucidate the action mechanism. PQM162 reduced the formation of ACF and AC in simultaneous treatments (dose of 1.0 mg/kg p.c) and post-treatment (doses of 1.0 and 2.0 mg/kg p.c). The hybrid led to reduced expression of TNF-α (Tumor Necrosis Factor) and COX-2 (Cyclooxygenase- 2). Furthermore, an increased expression of NRF2 (factor 2 related to nuclear erythroid factor 2) was found. No difference was found for KRAS genes (Ki-ras2 Kirsten rat viral sarcoma oncogene homolog), APC (Adenomatous polyposis coli), DNMT1 (DNA methyltransferase 1) and TP53 (p53 tumor suppressor). Immunohistochemical analysis showed that PQM162 reduced the expression of COX-2, PCNA (nuclear cell proliferation antigen) and β-catenin markers. On the other hand, PQM162 increased the expression of NRF2. In vitro, migration, cell cycle and apoptosis assays were performed in the HCT-8 colorectal adenocarcinoma lineage. PQM162 acts on cell migration processes, cell cycle arrest in G2/M and promotion of apoptosis. The results obtained suggest that PQM162 has chemopreventive and chemotherapeutic potential in colorectal carcinogenesis, acting in anti-inflammatory, antioxidant and cell proliferation pathways.